1974
DOI: 10.1084/jem.140.6.1511
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Cytotoxic T Lymphocytes in Vitro

Abstract: The cell-mediated immune response to primary allogeneic stimulation is characterized by the appearance of cytotoxic T lymphocytes (CTL) 1 (see reference 1 for review). Recently, the existence of anamnestic CTL responses to allografts has been suggested by studies in which the ability of normal and alloimmune spleen cells to respond to relevant alloantigens both in vivo (2, 3) and in vitro (4) was quantitatively compared. In other studies, physical characterization of CTL in the spleens of mice undergoing tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

1975
1975
2000
2000

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(22 citation statements)
references
References 14 publications
1
21
0
Order By: Relevance
“…That this correlation is also true in the case of MLC cells is further substantiated by comparing the FLS distributions of lymphoblasts and lymphocytes observed in this report with the distributions obtained when MLC cells are separated by velocity sedimentation at unit gravity, a technique which has been clearly shown to depend primarily on rz (8). In the latter case, we have previously shown that the modal sedimentation velocities of small T lymphocytes and T lymphoblasts are about 4 mm/hr and 6 mm/hr, respectively (5,6). This relative difference of 1.5-fold in 2 independently derived parameters related to r' would thus imply that the modal radius of T lymphoblasts exceeds that of small T lymphocytes by approximately 22%.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…That this correlation is also true in the case of MLC cells is further substantiated by comparing the FLS distributions of lymphoblasts and lymphocytes observed in this report with the distributions obtained when MLC cells are separated by velocity sedimentation at unit gravity, a technique which has been clearly shown to depend primarily on rz (8). In the latter case, we have previously shown that the modal sedimentation velocities of small T lymphocytes and T lymphoblasts are about 4 mm/hr and 6 mm/hr, respectively (5,6). This relative difference of 1.5-fold in 2 independently derived parameters related to r' would thus imply that the modal radius of T lymphoblasts exceeds that of small T lymphocytes by approximately 22%.…”
Section: Discussionmentioning
confidence: 78%
“…From previous studies in which day 5 MLC cells were separated by velocity sedimentation at unit gravity (5,6), it was established Figure 2. Modal FLS channel numbers for the two peaks were determined from the gated histograms.…”
Section: Resultsmentioning
confidence: 99%
“…4) that the precursor cells for cytotoxic cells underwent size transitions after embryonic antigen challenge/removal in a manner reminiscent of that seen with lymphocytes from animals primed with cells differing at the MHC (see MacDonald et al, 1974;Hayry and Anderson, 1975;Hollander et al, 1974). Furthermore, both tumour bearer/pregnant animals and animals early after removal of in vivo antigen challenge were found to contain a population of cells with peak sedimentation velocity (4 5-7 0 mm/h) which could preferentially inhibit a response to embryoassociated determinants (relative to the response to allo-antigen determinants)-see Table II.…”
Section: Discussionmentioning
confidence: 99%
“…In an auxiliary test of the similarity of the findings in tumour-related and pregnant mice, we have examined the specificity of cytotoxicity to fibroblast targets of lymphocytes from tumour-resected animals re-stimulated in culture with either Comparison of these data with those of Figs (Hayry and Anderson, 1975;Hollander, Ginsburg and Feldman, 1974;MacDonald, Cerottini and Brunner, 1974). The data collected from such studies have led to the concept of alternate cycles of blastogenesis (and development of cytotoxic potential) followed by quiescence (and a return to inactive small cells).…”
Section: Specificity Of Re-stimulation Of Embryoprimed Cells In Tissumentioning
confidence: 99%
“…For this reason, the Macdonald and/or Fitch hypotheses should be kept in mind when considering the case in hand. Of these two hypotheses we tend to prefer the first, since pre-killers, mature effectors and memory cells were shown (Macdonald et at., 1974b) to exist in different stages of cellular differentiation, where precursors and memory cells are high-density small lymphocytes and effectors are characterized as large, lower-density lymphocytes.…”
Section: Significance Of Ctl After Various Immunizing Proceduresmentioning
confidence: 97%